Association between homicide rates and suicide rates: a countrywide longitudinal analysis of 5507 Brazilian municipalities - Delan Devakumar; Mauricio L Barreto; Glyn Lewis; Daiane Borges Machado; Keltie McDonald; Luis F S Castro-de-Araujo; Lígia Kiss (BMJ Open, 2020)
Objective To estimate the association between homicide and suicide rates in Brazilian municipalities over a period of 7 years.Design We conducted a longitudinal ecological study using annual mortality data from 5507 Brazilian municipalities between 2008 and 2014. Multivariable negative binomial regression models were used to examine the relationship between homicide and suicide rates. Robustness of results was explored using sensitivity analyses to examine the influence of data quality, population size, age and sex on the relationship between homicide and suicide rates.Setting A nationwide study of municipality-level data.Participants Mortality data and corresponding population estimates for municipal populations aged 10 years and older.Primary and secondary outcome measures Age-standardised suicide rates per 100 000.Results Municipal suicide rates were positively associated with municipal homicide rates; after adjusting for socioeconomic and demographic factors, a doubling of the homicide rate was associated with 22% increase in suicide rate (rate ratio=1.22, 95% CI: 1.13 to 1.33). A dose–response effect was observed with 4% increase in suicide rates at the third quintile, 9% at the fourth quintile and 12% at the highest quintile of homicide rates compared with the lowest quintile. The observed effect estimates were robust to sensitivity analyses.Conclusions Municipalities with higher homicide rates have higher suicide rates and the relationship between homicide and suicide rates in Brazil exists independently of many sociodemographic and socioeconomic factors. Our results are in line with the hypothesis that changes in homicide rates lead to changes in suicide rates, although a causal association cannot be established from this study. Suicide and homicide rates have increased in Brazil despite increased community mental health support and incarceration, respectively; therefore, new avenues for intervention are needed. The identification of a positive relationship between homicide and suicide rates suggests that population-based interventions to reduce homicide rates may also reduce suicide rates in Brazil.